2010
DOI: 10.1111/j.1467-8551.2010.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Board Independence and CEO Duality on Firm Performance: A Quantile Regression Analysis for Indonesia, Malaysia, South Korea and Thailand

Abstract: We study the effect of board independence and CEO duality on firm performance for a sample of stock-listed enterprises from Indonesia, Malaysia, South Korea and Thailand, applying quantile regression. Quantile regression is more powerful than classical linear regression since quantile regression can produce estimates for all conditional quantiles of the distribution of a response variable, whereas classical linear regression only estimates the conditional mean effects of a response variable. Moreover, quantile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
149
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(166 citation statements)
references
References 99 publications
14
149
3
Order By: Relevance
“…The presence of non-executive directors on board gives a positive signal to the investors and shareholders in particular and stakeholders in general that affairs of the firms are prudently monitored which also increase public confidence and subsequently add to firm value (Hassan & Butt, 2009). According to agency theory the large proportion of independent directors affect positively the value of firm (Ramdani & Van, 2009). The presence of independent directors on board will insure the effective timely monitoring and will also safeguard the interests of shareholders and in most of the times leads to on merit selection of CEO to run the organization (Khan & Awan, 2012).…”
Section: Board Independencementioning
confidence: 99%
“…The presence of non-executive directors on board gives a positive signal to the investors and shareholders in particular and stakeholders in general that affairs of the firms are prudently monitored which also increase public confidence and subsequently add to firm value (Hassan & Butt, 2009). According to agency theory the large proportion of independent directors affect positively the value of firm (Ramdani & Van, 2009). The presence of independent directors on board will insure the effective timely monitoring and will also safeguard the interests of shareholders and in most of the times leads to on merit selection of CEO to run the organization (Khan & Awan, 2012).…”
Section: Board Independencementioning
confidence: 99%
“…In contrast, Ramdani & Witteloostuijn (2010) concluded that CEO-duality improves performance for mediocre enterprises. CEO who is the manager of the company is expected to choose high quality audit as a mechanism to increase their compensation (Francis & Wilson, 1988).…”
Section: Ceo-dualitymentioning
confidence: 99%
“…Agency theory states that when a board is composed mainly of outside directors, its efficiency leads to excellent FP (Ramdani and Witteloostuijn, 2010). Previous studies have discussed board composition to a large extent, and examined the association between board composition and FP, obtaining mixed results.…”
Section: Board Compositionmentioning
confidence: 99%